The influence of area reduction and commercial forestry on epigaeic invertebrate communities of Afromontane forest in the KwaZulu-Natal midlands. - Bourquin, Sven. (2013)
This study investigates the effects of forest fragmentation and matrix type on the diversity and distribution of epigaeic invertebrates in selected Afromontane forests of the KwaZulu-Natal midlands. The consequences of area reduction and matrix transformation, due to commercial forestry, for epigaeic invertebrate diversity, and the role of small forest fragments in their conservation, are particularly examined. Data are used to provide guidelines for the management and conservation of Afromontane forest and adjacent land use. Epigaeic invertebrates were sampled using pitfall-trapping quadrats set along gradsect lines in eleven Afromontane mistbelt mixed Podocarpus forests, five of which were surrounded by commercial pine, and five surrounded by the natural grassland matrix. The two sets of five forests were approximately matched in pairs by area (0.5ha to 215ha) and compared for differences in the epigaeic invertebrate communities to determine potential effects of fragmentation and landscape transformation on these communities. A large tract of forest (Leopards Bush Private Nature Reserve, 705ha, hereafter Leopards Bush) situated within the continuous Karkloof forest, served as the control. Trapping intensity increased with forest area. Invertebrates were identified to morphospecies, and where possible, further identification was carried out by specialists. A total of 61 282 epigaeic invertebrates, representing 168 morphospecies, were collected. There was a significant positive species-area effect evident in the Balgowan complex (grassland matrix), but not in the Gilboa complex (pine matrix). There was thus a confounding influence of the pine matrix in the Gilboa, since the matrix represented the single most important difference between the two forest complexes. In afforested landscapes it is thus crucial to conserve the largest intact forest fragments to preserve overall epigaeic invertebrate species richness. Density compensation was evident in the Balgowan complex but not in the Gilboa complex. Recolonisation dynamics may play a small role in the regional persistence of a species within forest in a pine matrix, and persistence would be ensured by the preservation of a small number of large forest fragments containing large, extinction-resistant populations. The establishment of ecologically functional grassland corridors (i.e. wide enough to maintain "natural" ecological processes) between mistbelt mixed Podocarpus forest fragments would facilitate dispersal of epigaeic invertebrates between forest fragments. The results of this study indicated that edge effects were experienced deeper in the forests than the expected 32m suggested by Kotze and Samways (1999) and thus any changes to the epigaeic invertebrate communities induced by edge effects had already taken place inthese forests. Cluster analyses revealed that twenty-two percent (n = 37) of invertebrate species recorded were common to all forests and these shared species were generalist feeders. The effect of matrix type on diversity of epigaeic invertebrate communities was most notable for large forests (i.e. over 30 ha). Large fragments with core areas unaffected by edge-induced disturbance would support more forest dependent species than small fragments due to a lower susceptibility to invasions. Although not significantly nested, epigaeic invertebrate communities in both forest complexes tended toward nestedness. Isolation of forest fragments appeared to play a lesser role than patch area in determining the invertebrate community composition. Assuming that communities are extinction-dominated, community convergence in small fragments has probably already occurred, with invasions from the matrix confounding patterns of deterministic extinction of forest-dependent epigaeic invertebrate species. A habitat disturbance gradient was evident from the relatively undisturbed control (Karkloof quadrats) to the more disturbed pine dominated Gilboa quadrats, with intermediate disturbance values for the Balgowan (natural grassland matrix) fragments. The undisturbed Karkloof forest was characterised by a deep, abundant leaf litter layer, dense sub-canopy, and an abundance of seedlings indicating high rates of natural regeneration. Leaf litter depth was the most important variable in explaining the variation of epigaeic invertebrate species. A "shopping basket" of eight selected ecological indicators are mostly unrelated species. In general, this study supports the wealth of evidence advocating the use of epigaeic invertebrates, especially Carabid and Staphylinid beetles, as ecological indicators. In this study, eight species were identified by canonical correspondence analysis as ecological indicators that were sensitive to forest disturbance. This suite of species in the mistbelt mixed Podocarpus forests of the KwaZulu-Natal midlands will provide an accurate indication of forest condition in summer when abundance data is used. === Thesis (M.Sc.)-University of Natal, Pietermaritzburg, 2001.